2018
DOI: 10.1371/journal.pone.0198154
|View full text |Cite|
|
Sign up to set email alerts
|

Sustained AAV9-mediated expression of a non-self protein in the CNS of non-human primates after immunomodulation

Abstract: A critical issue in transgene delivery studies is immune reactivity to the transgene- encoded protein and its impact on sustained gene expression. Here, we test the hypothesis that immunomodulation by rapamycin can decrease immune reactivity after intrathecal AAV9 delivery of a transgene (GFP) in non-human primates, resulting in sustained GFP expression in the CNS. We show that rapamycin treatment clearly reduced the overall immunogenicity of the AAV9/GFP vector by lowering GFP- and AAV9-specific antibody resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In this study, we demonstrate that targeted transduction of Schwann cell of the peripheral nervous system can be achieved after a single lumbar intrathecal injection using the AAV9. AAV9 has been previously used mostly for CNS transduction [60] but has not been studied specifically for PNS targeting [61][62][63]. However, some studies showed that AAV9 can transduce peripheral nerves after intrathecal injection [64] with detection of EGFP expression in sciatic nerves after intravenous or intrathecal injection in mice [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrate that targeted transduction of Schwann cell of the peripheral nervous system can be achieved after a single lumbar intrathecal injection using the AAV9. AAV9 has been previously used mostly for CNS transduction [60] but has not been studied specifically for PNS targeting [61][62][63]. However, some studies showed that AAV9 can transduce peripheral nerves after intrathecal injection [64] with detection of EGFP expression in sciatic nerves after intravenous or intrathecal injection in mice [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the efficacy of intrathecal delivery in non-human primates are different depending on vectors and site of injection used. Ramsingh et al (2018) showed efficient transduction using AAV9 42 , while Hinderer et al (2020) showed that intrathecal injection of AAVrh78 failed to transduce the CNS in older animals using large injection volumes but was efficient in younger animals. In contrast, intra-cisterna magna injection proved to be efficient in both young and older animals at lower volumes 29 .…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 , 7 The etiology, pathogenesis, and clinical relevance of these findings are not fully understood and have not been consistently reported. 8 , 9 Furthermore, a 4-year study following intrathecal administration of AAV9.hIDUA to juvenile NHPs did not report DRG pathology, suggesting that either toxicity does not affect young animals or that the initial morphological changes resolve over time. 10 The cause of dorsal root ganglionopathy is unknown, but current hypotheses include either an immune response to the capsid or transgene product, protein overexpression, or vector quality, including varying levels of empty and full capsids that are generally dependent on the purification processes used.…”
Section: Introductionmentioning
confidence: 99%